Songs on the Road Wandering Religious Poets in India, Tibet, and Japan - Larsson, Stefan; af Edholm, Kristoffer (Stockholm Studies in Comparative Religion, 2021)
This book consists of seven chapters on the subject of poetry and itinerancy within the religious traditions of India, Tibet, and Japan from ancient to modern times. The chapters look, each from a different angle, at how itinerancy is reflected in religious poetry, what are the purposes of the wanderers' poems or songs, and how the wandering poets relate to local communities, sacred geography, and institutionalized religion. We encounter priest-poets in search of munificent patrons, renouncers and yogins who sing about the bliss and hardship of wandering alone in the wilderness, Hindu pilgrims and opponents of pilgrimage, antinomian Buddhist-Tantric poets from Bengal, and the originator of the haiku. We are led along roads travelled by many, as well as paths tread by few.